2020
DOI: 10.1186/s40900-020-00213-6
|View full text |Cite
|
Sign up to set email alerts
|

Guidance on authorship with and acknowledgement of patient partners in patient-oriented research

Abstract: The Strategy for Patient-Oriented Research Chronic Pain Network was founded in 2016 and is a patient-oriented research network funded by the Canadian Institutes of Health Research. The Network incorporates patient partners throughout its governance and operations meaning that patient partners may contribute to research projects in ways that warrant scientific authorship as defined by the International Committee of Medical Journal Editors. The Network did a brief informal review of guidance on patient authorshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 7 publications
0
53
0
Order By: Relevance
“…In this commentary, some members of this group and the study team share their reflections on their experiences, from inception through to closure of the group, which coincided with the duration of the study. We have written this commentary collaboratively, informed by publication and authorship recommendations provided by Richards et al [ 17 ]. The group was chaired by JW and supported by HC and RF.…”
Section: Introductionmentioning
confidence: 99%
“…In this commentary, some members of this group and the study team share their reflections on their experiences, from inception through to closure of the group, which coincided with the duration of the study. We have written this commentary collaboratively, informed by publication and authorship recommendations provided by Richards et al [ 17 ]. The group was chaired by JW and supported by HC and RF.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review, co-authored with patients, on patient involvement in research publications, identified 21 evidence-based recommendations to help minimize the potential risks and maximize the potential benefits of patient authorship [ 26 ]. Patient partners and researchers from the Chronic Pain Network have published a narrative review that provides guidance for patient and nonpatient authors on patient authorship [ 27 ]. More recently, based on demand by patient advocates for practical guidance on how to author peer-reviewed publications, international patient advocates and certified medical publication professionals created the first free online ‘Patients in Publications’ training course for patient advocates (launched in June 2021) [ 28 , 29 ].…”
Section: Emerging Evidence and Guidance On Patient Authorshipmentioning
confidence: 99%
“…Alternatively, new guidance specific to patient partners could be developed. Recently, the Strategy for Patient-Oriented Research Chronic Pain Network, which is funded by the Canadian Institutes of Health Research, shared a Guidance document on authorship with and acknowledgement of patient partners in patient-oriented research [ 19 ]. This document was co-developed by patients and researchers.…”
Section: Discussionmentioning
confidence: 99%